تقييم الإحتياجات التعليمية للأمهات الحوامل حول التغذية الصحية أثناء الحمل - عيسى, مروان (Latakia University Journal -Medical Sciences Series, 2018)
Healthy and balanced food during pregnancy helps to gain proper weight, growth and development of the fetus and helps to improve the birth product to be free from complications in pregnant or fetus. Pregnancy is important for providing and educating mothers about healthy nutrition during pregnancy. The importance of this study is to assess the knowledge and practices of pregnant women about healthy nutrition during pregnancy, which leads to the identification of deficiencies and the assessment of Educational Needs. This study was conducted on a sample of 150 pregnant women from the health center in Ramel shamali in Lattakia. They were selected in the appropriate non-randomized manner. The results of the study showed a lack of information about the effect of malnutrition on pregnant and fetus health, the main foods to be eaten during pregnancy, the main food sources and the appropriate weight gain during pregnancy, respectively (14%), (16%), (18%), (24%), as well as a lack of dietary practices in the areas of Eating iron and folic acid, eating low-fat meals, taking 3 servings Fruit, eat 3-4 servings of milk and dairy products, eating a half share of the meat) and which amounted respectively (26%), (36%), (30%), (18%) (16%). It is therefore proposed to design and implement education programs for pregnant women in health centers that correct the lack of information and practices related to healthy nutrition during pregnancy يساعد الغذاء الصحي و المتوازن اثناء الحمل في كسب الوزن الملائم, نمو و تطور الجنين, و تحسين نتاج الولادة ليكون خال من المضاعفات عند الحامل أو الجنين, و تعتبر فترة الحمل مهمة لتزويد وتثقيف الأمهات حول التغذية الصحية السليمة اثناء الحمل, لذلك يجب تحديد الإحتياجات التعليمية حول التغذية عند الحوامل لمساعدتهن على اكتساب المعلومات و الممارسات و الإتجاهات المناسبة فيما يتعلق بالتغذية أثناء الحمل, من هنا تأتي اهمية هذه الدراسة حول تقييم معلومات و ممارسات الحوامل حول التغذية الصحية أثناء الحمل الامر الذي يقود الى تحديد جوانب النقص فيها و بالتالي تقييم الاحتياجات التعليمية . أجرى هذا البحث على عينة قوامها 150 سيدة حامل من المراجعات للمركز الصحي في الرمل الشمالي في اللاذقية, تم اختيارهن بطريقة الأعثيان الملائم غير الاحتمالي, و أظهرت نتائج الدراسة وجود نقص في معلومات الحوامل حول تأثير سوء التغذية على صحة الحامل و الجنين, معرفة أنواع الأغذية الرئيسية الواجب تناولها أثناء الحمل, معرفة مصادر الأغذية الرئيسية, و معرفة كسب الوزن الملائم أثناء الحمل حيث بلغت النسب على التوالي (14%), (16%), (18%), (24%), بالإضافة لوجود نقص فيما يتعلق بالممارسات الغذائية في مجالات (تناول الحديد و حمض الفوليك, تناول وجبات قليلة الدهون, تناول 3 حصص من الفواكه, تناول 3-4 حصص من الحليب ومشتقاته, تناول نصف حصة من اللحوم ) و التي بلغت على التوالي (26% ),( 36%), (30%),(18%), (16%). لذلك اقترح تصميم و تنفيذ برامج تثقيفية للحوامل في المراكز الصحية ترمم النقص الحاصل في المعلومات و الممارسات المتعلقة بالتغذية الصحية أثناء الحمل.